Níveis de glicerina na fermentação in vitro de diferentes carboidratos e dietas - Amorim, Karitha Regiane Ribeiro de (2016)
This study aimed to evaluate the effects of glycerol inclusion levels in the fermentation of different carbohydrates and diets for ruminal microflora through the technique of in vitro gas production. The glycerine inclusion levels were zero, 10, 20 and 30% of the total amount of substrate incubated in vitro on fermentation purified energy substrates (cellulose, sucrose and starch), and on diets (grass forage Tanzania and the total diet containing 70% concentrate). And these were incubated in 120 ml flasks for 96 h at 39 °C under constant stirring, the gas pressure readings were made using a pressure transducer. The rumen fluid used in the incubation of substrates was derived from two sheep cannulated in the rumen fed diet containing 60% roughage and 40% concentrado. O ruminal fluid was collected and sent to the laboratory in thermos and their manipulation was made and the sprinkling CO2-free oxygen. At the end of incubations purified substrates measurement of pH was performed on the bottles, whereas the incubation of the diets was determined residual NDF. Were estimated total volumes of gas produced to glycerine, cellulose, sucrose and starch 124.80, 146.30, 169.64 and 158.24 ml, respectively, and the following degradation rate 0.0643 h -1, 0 , 1,0,0899 0306 h-1 and 0.0504 h-h1 and latency 10.88, 38.00, 2.56 and 7.33 h, respectively. Glycerin levels caused quadratic effect on the gas production (P <0.05) as well as on the rate of cellulose digestion and latency. Sucrose, glycerin levels also had a quadratic effect on the gas production (P <0.05), as well as latency, while the rate of digestion was not affected. For starch, glycerin levels promoted linear reduction of gas production (P <0.05) and quadratic effect on the latency, while the rate of digestion was not affected. Glycerin levels caused linear increase (P <0.05) in the vials containing pH of the starch as a substrate, and linear decreasing pH when the pulp was the substrate. As for the sucrose no significant effect. There was no effect of glycerin levels associated with forage on the kinetic parameters in vitro gas production (P> 0.05), and estimated average values of 100.14 mL, 0.03425 h -1 and 13,63h, for the final gas volume, digest and latency. No significant levels of glycerine by total diet on total gas or the rate of digestion, but the latency was increased linearly (P <0.05) according to the glycerine levels. Glycerin levels shown a linear decrease (P <.05) NDF digestion for the total diet but did not affect (P> 0.05) the digestion of forage NDF.